Transmitter inputs to different motoneuron subgroups in the oculomotor and trochlear nucleus in monkey - Christina Zeeh; Michael J. Mustari; Bernhard J. Hess; Anja K.E. Horn (Frontiers Media S.A., 2015)
In all vertebrates the eyes are moved by six pairs of extraocular muscles enabling horizontal, vertical and rotatory movements. Recent work showed that each extraocular muscle is controlled by two motoneuronal groups: 1. Motoneurons of singly-innervated muscle fibers (SIF) that lie within the boundaries of motonuclei mediating a fast muscle contraction and 2. motoneurons of multiply-innervated muscle fibers (MIF) in the periphery of motonuclei mediating a tonic muscle contraction. Currently only limited data about the transmitter inputs to the SIF and MIF motoneurons are available. Here we performed a quantitative study on the transmitter inputs to SIF and MIF motoneurons of individual muscles in the oculomotor and trochlear nucleus in monkey. Pre-labeled motoneurons were immunostained for GABA, glutamate decarboxylase, GABA-A receptor, glycine transporter 2, glycine receptor 1, and vesicular glutamate transporters (vGlut) 1 and 2. The main findings were: 1. the inhibitory control of SIF motoneurons for horizontal and vertical eye movements differs. Unlike in previous primate studies a considerable GABAergic input was found to all SIF motoneuronal groups, whereas a glycinergic input was confined to motoneurons of the medial rectus muscle mediating horizontal eye movements and to those of the levator palpebrae muscle elevating the upper eyelid. Whereas SIF and MIF motoneurons of individual eye muscles do not differ numerically in their GABAergic, glycinergic and vGlut2 input, vGlut1 containing terminals densely covered the supraoculomotor area targeting medial rectus MIF motoneurons. It is reasonable to assume that the vGlut1 input affects the near response system in the supraoculomotor area, which houses the preganglionic neurons mediating pupillary constriction and accommodation and the medial rectus MIF motoneurones involved in vergence.